2018
DOI: 10.1111/jvim.15312
|View full text |Cite
|
Sign up to set email alerts
|

Two mixed breed dogs with sensory neuropathy are homozygous for an inversion disruptingFAM134Bpreviously identified in Border Collies

Abstract: Two unrelated 8‐month‐old male mixed breed dogs were presented for evaluation of progressive ataxia, knuckling, and lack of pain perception in the distal limbs. Because of the similarity in age of onset, progression, and clinical findings with previously described sensory neuropathy in Border Collies, the affected dogs were screened for an FAM134B mutation and were determined to be homozygous for the mutation. Despite few phenotypic similarities with other breeds, genetic testing for specific diseases should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…A genome‐wide association study revealed the disruption of the FAM134B gene due to an inversion in Border Collies with neurological diseases (Forman et al, 2016). Amengual‐Batle et al (2018) also reported homozygous mutations of FAM134B in two unrelated 8‐month‐old male mixed‐breed dogs who showed the same symptoms as the border collie with sensory neuropathy described by Forman et al (2016).…”
Section: Role Of Fam134b In Organelle Membrane Morphogenesis and Diseasesmentioning
confidence: 69%
“…A genome‐wide association study revealed the disruption of the FAM134B gene due to an inversion in Border Collies with neurological diseases (Forman et al, 2016). Amengual‐Batle et al (2018) also reported homozygous mutations of FAM134B in two unrelated 8‐month‐old male mixed‐breed dogs who showed the same symptoms as the border collie with sensory neuropathy described by Forman et al (2016).…”
Section: Role Of Fam134b In Organelle Membrane Morphogenesis and Diseasesmentioning
confidence: 69%
“…This finding is consistent with a polymorphic, but benign, microsatellite marker, and this WNK1 variant therefore was excluded from further examination. RETREG1 was reported previously to cause sensory neuropathy in dogs 5,9 and humans 31 . The variant in RETREG1 therefore remains the strongest candidate variant and was retained for further investigation.…”
Section: Resultsmentioning
confidence: 90%
“…Although HSANs have been reported in different dog breeds including Border Collie, 5‐8 Border Collie cross, 9 Long‐haired Dachshund, 10,11 Miniature Pincher, 12 Jack Russell Terrier, 13 Pointer, 14‐17 English Springer Spaniel, 17 French Spaniel, 17,18 and Fox Terrier, 4 only 2 causal variants have been identified to date. The first is an inversion disrupting RETREG1 ( reticulophagy regulator 1 ), encoding a Golgi protein, in Border Collies and Border Collie crosses (Online Mendelian Inheritance in Animals [OMIA] 002032‐9615) 5,9 . The second is a point variant in a lincRNA upstream of the GDNF gene encoding glial cell‐derived neurotrophic factor in the Pointer, English Springer Spaniel, and French Spaniel (OMIA 001514‐9615) 17 …”
Section: Introductionmentioning
confidence: 99%
“…Older neuropathies, such as the well-known inherited sensory and autonomic in the Border Collie first described in 1987 (Wheeler, 1987), have also benefited from genetic advances. In 2016 one causal genetic variant of FAM134B , which encodes a cis -Golgi protein found in sensory and autonomic ganglion neurons, has been discovered (Forman et al, 2016) and two-years later, this mutation was also described in two mixed breed dogs (Amengual-Batle et al, 2018). In four other breeds, the German short-haired Pointer, the English Pointer, the English Springer Spaniel and the French Spaniel, some known since 1964, a similar inherited sensory and autonomic exist and found to be linked to a genetic variation of the long-non-coding RNA located upstream of the Glial cell-Derived Neurotrophic Factor gene, coding for a neurotrophic factor involved in neuronal development and adult neuronal survival (Plassais et al, 2016).…”
Section: Introductionmentioning
confidence: 99%